2018
DOI: 10.1515/macvetrev-2017-0029
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Endoparasites by Faecal Examination in the Wild Boar Population in Vojvodina (Serbia)

Abstract: The aim of our study was to determine whether and to what extent certain species of helminths and protozoa are present in the wild boar population living in hunting grounds in Vojvodina. For this purpose, 52 faecal samples of hunted wild boars (aged 6 months to 2 years) were examined. Examination of the faeces was performed using classical coproscopic laboratory methods. The following parasite species were identified: Metastrongylus spp. Ascaris suum, Trichuris suis, Physocephalus sexalatus, Strongyloides rans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 19 publications
0
5
0
2
Order By: Relevance
“…Conforme descrito acima, 57,7% dos suídeos avaliados apresentaram amostras positivas nas análises coproparasitológicas (Tabela 1), sendo esta uma taxa de infecção ligeiramente inferior às reportadas em estudos similares. Suídeos asselvajados amostrados na Sérvia apresentaram elevada positividade (88,46%) em amostras de fezes (n=52) avaliadas pelas técnicas de sedimentação simples e flutuação com sulfato de zinco (STOJANOV et al, 2018). De forma similar, Spieler & Schnyder (2021) encontraram 77,4% de positividade em amostra fezes (n=55) de suídeos asselvajados, amostrados na Suíça, utilizando-se as técnicas de sedimentação, flutuação e método mini-flotac, nesse estudo eles evidenciaram a presença de Metantrongylus sp.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Conforme descrito acima, 57,7% dos suídeos avaliados apresentaram amostras positivas nas análises coproparasitológicas (Tabela 1), sendo esta uma taxa de infecção ligeiramente inferior às reportadas em estudos similares. Suídeos asselvajados amostrados na Sérvia apresentaram elevada positividade (88,46%) em amostras de fezes (n=52) avaliadas pelas técnicas de sedimentação simples e flutuação com sulfato de zinco (STOJANOV et al, 2018). De forma similar, Spieler & Schnyder (2021) encontraram 77,4% de positividade em amostra fezes (n=55) de suídeos asselvajados, amostrados na Suíça, utilizando-se as técnicas de sedimentação, flutuação e método mini-flotac, nesse estudo eles evidenciaram a presença de Metantrongylus sp.…”
Section: Resultsunclassified
“…Já a técnica de Gordon e Whitlock (utilizando a câmera de McMaster e o cálculo de número de ovos por grama de fezes-OPG) foi utilizada a fim de estimar a carga parasitária presente. Todas as técnicas foram realizadas conforme descrito em Monteiro (2017); Stojanov et al (2018) e Mundim et al (2004). Os ectoparasitas e os endoparasitas encontrados foram identificados por meio de chaves taxonômicas, a fim de definir o gênero das espécimes coletadas e seu ciclo de vida, a identificação dos ovos presente nas fezes deu-se por meio de observação morfológica qualitativa, conforme Dantas-Torres et al ( 2019), Monteiro (2017) e Thienpont et al (1979).…”
Section: Methodsunclassified
“…Our study documented no difference in the prevalence from different host sexgroups (P 0.05) (Table 2) and between age groups, except for Metastrongylus Pedondotectus and Metastrongylus Confusus (P 0.05). Stojanov et al (2018) reported that the degree of the infection was greater in female than in male wild boars, which is explained by the development of the immune response to certain parasitic species.…”
Section: Resultsmentioning
confidence: 99%
“…in fecal samples from pigs of different ages. Stojanov et al (2018) registered a prevalence of 30% of Globocephalu sp. in pigs in Serbia.…”
Section: /10mentioning
confidence: 99%